1990
DOI: 10.1148/radiology.175.2.2183286
|View full text |Cite
|
Sign up to set email alerts
|

Ciliated hepatic foregut cyst: radiologic features.

Abstract: Ciliated hepatic foregut cysts (CHFCs) are solitary unilocular cysts in the liver that are histologically similar to bronchogenic cysts. Three cases of CHFC are reported that demonstrated radiologic features similar to those of solid masses. All the lesions were smaller than 3 cm in diameter and were subcapsular. At ultrasonography, one lesion appeared anechoic but the other two were hypoechoic. Unenhanced computed tomography demonstrated the lesions to be hyperattenuating or isoattenuating relative to surroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 0 publications
2
39
1
1
Order By: Relevance
“…24,25 The prevalence of hepatic mucinous cystic neoplasm in segment IV may support an implant origin because hamartomatous lesions commonly develop in segment IV. 26,27 The expression of oestrogen receptor or PgR in ovarianlike stroma also supports a putative role for female hormones in the tumorigenesis. 28 In conclusion, hepatic mucinous cystic neoplasms and biliary intraductal papillary neoplasms have different clinicopathological characteristics as evidenced by differences in the age and gender of patients, macroscopic appearance, immunophenotypes, and grades of malignancy.…”
Section: Discussionmentioning
confidence: 85%
“…24,25 The prevalence of hepatic mucinous cystic neoplasm in segment IV may support an implant origin because hamartomatous lesions commonly develop in segment IV. 26,27 The expression of oestrogen receptor or PgR in ovarianlike stroma also supports a putative role for female hormones in the tumorigenesis. 28 In conclusion, hepatic mucinous cystic neoplasms and biliary intraductal papillary neoplasms have different clinicopathological characteristics as evidenced by differences in the age and gender of patients, macroscopic appearance, immunophenotypes, and grades of malignancy.…”
Section: Discussionmentioning
confidence: 85%
“…Previous reports indicate that the ciliated foregut cysts in the liver are not enhanced after the injection of contrast material (8). In another case, a study of the gallbladder found that no enhancement was seen for the same finding of a contrast-enhanced CT (5).…”
Section: Discussionmentioning
confidence: 93%
“…Radiologically, CHFC tends to be hypoechoic on ultrasound, and iso-to hyperattenuating on unenhanced CT and does not contrast-enhance [13,14]. On MRI imaging, cysts have been reported to be hyper-, hypo-, and isodense on T1 imaging and may be markedly hyperintense or isointense on T2 imaging [15].…”
Section: Discussionmentioning
confidence: 99%